Hubungan Antara Optimisme Dengan Stres Akademik Pada Mahasiswa Tingkat Akhir - Jenny eka Puspita; Ni Wayan Sukmawati Puspitadewi (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates the relationship between optimism and academic stress among final-year university students using a quantitative correlational design. The research involved 120 respondents selected through accidental sampling, focusing on students currently engaged in thesis completion, a phase characterized by high academic pressure. Data were collected using Likert-based instruments measuring dispositional optimism and academic stress, both demonstrating acceptable reliability coefficients. The findings reveal a significant negative correlation between optimism and academic stress (r = -0.594, p < 0.01), indicating that higher levels of optimism are associated with lower levels of stress. The coefficient of determination shows that optimism contributes 35.3% to the variance in academic stress, suggesting a meaningful predictive role. The distribution patterns further highlight variability in psychological responses among students, reflecting differences in coping capacity and cognitive appraisal. These results support cognitive and self-regulation theories, emphasizing optimism as a protective psychological factor that enhances resilience and adaptive coping in demanding academic contexts, particularly during the completion of final academic requirements